Characteristics of syphilitic uveitis in northern China - Zhang, Xiaomin (BMC Ophthalmol, 2017)
BACKGROUND: To describe the characteristics of patients with syphilitic uveitis in northern China. METHODS: A case series of 21 patients (33 eyes) diagnosed with syphilitic uveitis from 2011 to 2016 at a tertiary center in northern China was retrospectively analyzed. RESULTS: Twenty-one patients (33 eyes) were diagnosed as syphilitic uveitis. Posterior segment involvement was found in 32 eyes (97.0%). Vitreous haze, neuroretinitis, and posterior placoid chorioretinitis were mainly found in patients with a relatively short duration of the disease, while diffuse chorioretinitis, pseudoretinitis pigmentosa, cystoid macular edema, and epiretinal membrane were found in patients with relatively long duration of ocular involvement. A low best-corrected visual acuity (P = 0.022) and a delay of syphilis treatment (P < 0.001) were associated with a significantly worse visual outcome. CONCLUSIONS: Syphilitic uveitis should be included in the differential diagnosis of any form of posterior ocular inflammation. The pattern of ocular involvement may change with the disease progression.